Tribological study of high bearing blended polymer-based coatings for air-conditioning and refrigeration compressors (2011)
Deposition by spray techniques has made possible to coat different substrate materials found in engineering applications, such as air-conditioning and refrigeration compressors, with blended soft polymeric coatings based on polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE), and fluorocarbons (FC). In this study, the tribological performance of four polymeric coatings (PEEK/PTFE, PTFE/MoS2, FC, and PEEK/Ceramic against 52100 steel) was evaluated using a specialized tribo meter simulating aggressive compressor conditions. Experimental results showed that PTFE/MoS2, and PEEK/PTFE coating systems performed better in terms of their tribological performance compared to the other polymeric coatings under starved lubricated conditions (mixture of R-134a refrigerant and polyalkylene glycol lubricant). Under aggressive unlubricated conditions, scuffing was observed for all the coatings except PEEK/PTFE. By using time-of-flight secondary ion mass spectrometry (TOF-SIMS) and X-ray diffraction (XRD), it was found that the good performance of PEEK/PTFE was related to the formation of chemical species from the fragmentation of PTFE, PEEK, and its favorable interaction with the substrate, along with an increase in crystallization of PEEK during testing